(untitled) (Medicine Today, 2023)
Introduction: Yolk sac are a rare type of germ cell tumors that occurs most commonly in prepubertal age but are rare in adults. Case report: We present a case of a yolk sac tumor in a 25-year-old man with a history of bilateral cryptorchidism diagnosed at the age of 10 for which bilateral orchidopexy was done at the age of 19. Discussion: Delayed diagnosis of cryptorchidism are common in developing countries. Most adults with cryptorchidism prefer orchidopexy instead of orchiectomy. Due to a lack of adherence to follow-up, late presentation with complications is common. Conclusion: Yolk sac tumor can rarely occur in cryptorchid testis after post-pubertal orchidopexy. As lack of adherence to follow-up is common in developing countries, orchidopexy should be avoided. Medicine Today 2023 Vol.35(1): 67-69